2020
DOI: 10.4149/bll_2020_092
|View full text |Cite
|
Sign up to set email alerts
|

The role of miRNAs targeting K-ras and APC genes in colorectal cancer

Abstract: OBJECTIVES: The occurrence of abnormal expression patterns in different types of cancer suggests that micro RNAs (miRNAs) may play an important role in tumorigenesis. The aim of this study was to examine the expression levels of miRNAs known to be associated with the regulation of the expression levels of the APC and K-ras, which are important in the development of colorectal cancer (CRC). METHODS: The expression levels of miR-27, miR-663, miR-217, miR-181d, APC and K-ras in the serum, tumor and adjacent tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…K-RAS mutations occur on exons 2, 3, and 4, and exon 2 is a common mutation site for K-RAS mutations. The mutation of K-RAS gene is a common oncogene in CRC, and the incidence of mutation in Asians is 29–62.9% [ 23 , 24 ]. Various genes, such as EGFR and K-RAS, are involved in the occurrence of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…K-RAS mutations occur on exons 2, 3, and 4, and exon 2 is a common mutation site for K-RAS mutations. The mutation of K-RAS gene is a common oncogene in CRC, and the incidence of mutation in Asians is 29–62.9% [ 23 , 24 ]. Various genes, such as EGFR and K-RAS, are involved in the occurrence of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-663 is reportedly involved in many important pathological processes, especially in cancer. 20 MiR-663 plays an important regulatory role in ovarian cancer and can promote disease progression by targeting TUSC2. 19 MiR-663 has been reported to affect apoptosis by controlling mitochondrial outer membrane permeability (MOMP) by directly targeting PUMA/BBC3 and BTG2 in non-small cell lung cancer (NSCLC) and acts as an oncogene in this disease.…”
Section: Discussionmentioning
confidence: 99%
“…There is a regulatory feedback: miR-181d regulates the secretion of KLK6, and its expression decreases when KLK6 is knocked down [80]. However, miR-181d was also found to be upregulated in CRC and involved in the post-transcriptional regulation of c-MYC by targeting FBXL3 and CRY2, as well as in the regulation of KRAS expression [82][83][84][85]. One of these studies identified miR-181d as possibly a onco-miRNA in CRC, which seems to be contrary to the above studies [82].…”
Section: Bidirectionally Regulated Mirnasmentioning
confidence: 99%